Do You See What I See? Exploring Vividness of Visual Mental Imagery in Product Design Ideation. (May 2022) - Hart, E.; Hay, L.
Abstract: This paper reports a preliminary study (N=16) exploring vividness of visual mental imagery in product design ideation. Vividness was observed to vary across designers in the study, from high (68.8% of participants) to moderate (18.8%) to low (12.5%). A significant, strong positive relationship was found between vividness and creativity. Most participants reported using imagery always or sometimes, except one who has difficulties forming mental images. The results have several implications, including the possibility of other 'ways of imagining' not captured by visual reasoning models of design.